TASTE MY TEARS: Received: 1st October 2021; Revised: 03rd March 2022; Accepted: 15th March 2022 - Zeidan, Samer Ratib (PEOPLE: International Journal of Social Sciences, 2022)
The poem focuses on the pains of the heart and the tragedy an orphaned soul would feel. It aims to put the feelings into words to give a voice to emotions and to the people who suffer from similar problems but are unable to voice them. The methodologies used are not many and are primarily related to poetry and rhyme scheme. The poet moves on to describe how his soul is orphaned. Alone in this world, the soul is without a guide to ease his passage and lead one to his or her lover. In his tears, his final hopes remain that she will be able to share his fantasies and love with him by tasting them and feeling the embrace and kiss that he sent her, along with the emotions he sustained inside his salty droplets. That kiss is the same one that concealed his desolation and sins for far too long, and that kept those aching distresses that plagued his heart invisible to the people around him for inside, hope remained that he shall find a way to reach his lover and lay his eyes upon her—concluding that love reigns above all.